The impact of variable sea ice roughness on changes in Arctic Ocean surface stress: A model study. Issue 3 (26th March 2016) - Martin, Torge; Tsamados, Michel; Schroeder, David; Feltham, Daniel L.
Abstract: The Arctic sea ice cover is thinning and retreating, causing changes in surface roughness that in turn modify the momentum flux from the atmosphere through the ice into the ocean. New model simulations comprising variable sea ice drag coefficients for both the air and water interface demonstrate that the heterogeneity in sea ice surface roughness significantly impacts the spatial distribution and trends of ocean surface stress during the last decades. Simulations with constant sea ice drag coefficients as used in most climate models show an increase in annual mean ocean surface stress (0.003 N/m 2 per decade, 4.6%) due to the reduction of ice thickness leading to a weakening of the ice and accelerated ice drift. In contrast, with variable drag coefficients our simulations show annual mean ocean surface stress is declining at a rate of −0.002 N/m 2 per decade (3.1%) over the period 1980–2013 because of a significant reduction in surface roughness associated with an increasingly thinner and younger sea ice cover. The effectiveness of sea ice in transferring momentum does not only depend on its resistive strength against the wind forcing but is also set by its top and bottom surface roughness varying with ice types and ice conditions. This reveals the need to account for sea ice surface roughness variations in climate simulations in order to correctly represent the implications of sea ice loss under global warming. Key Points: Recent decrease in form drag reduces Arctic Ocean surface stress Sea ice strength and form drag decline both driven by ice thinning but with competing effects on ocean surface stress Modeling variable ice roughness reveals damping/amplifying effect of sea ice on momentum transfer